Infark Serebri Tipe Kardioemboli pada Pasien dengan Fibrilasi Atrium - ERIC HARTONO TEDYANTO; KEN CHRISTIAN KAWILARANG; FEISAL TANJUNG (Universitas Hang Tuah, 2020)
Abstract Background: Stroke is the leading cause of disability and the second most common cause of death in the world. Atrial fibrillation (AF) is the major risk factor for embolic stroke. Patients with atrial fibrillation have a 5 times much more risk of stroke to those who do not have atrial fibrillation. Case Report: A 40-year-old woman came to the Emergency Unit with chief complaints the left-sided limbs suddenly weakened while cooking. On ECG examination there is an irregular rhythm (irregular P-P), leading to an atrial fibrillation. CT scan revealed hypodense lesions on the temporal part of the left side, leading to a cerebral infarction. Discussion: AF puts patients at an increased risk for stroke because blood cannot be properly pumped, which caused stagnation and formed a blood clot. This clot can be released from ventricle and travel to the other organ via artery, including brain and block the blood flow which can result a infarct stroke. Conclusion: Close supervision and routine control are needed for patients with heart rhythm disorders, especially atrial fibrillation to prevent embolic stroke